Early Analysis of Standard Learning Process at Polytechnic Kemenkes Semarang - Sugiyanto Sugiyanto; Supriyana Supriyana; Lanny Sunarjo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
This study is descriptive (quantitative and qualitative) with the survey approach and aims to determine the criteria for implementation of the learning process Polytechnic Kemenkes Semarang and identify educational issues include resource management, learning systems, learning models and the availability of learning tools . The population was civitas Akademika Polytechnic Kemenkes Semarang, covering 23 study program, 265 faculty and 1320 students. Samples obtained by random sampling technique, Prodi = 17 pcs (75%), lecturers = 35 people (15%) and student = 295 people (25%). Problems of education is a major obstacle to the improvement and quality assurance of learning readiness among other lecturers in the learning process is not optimal and the supporting infrastructure of academic inadequate. It is recommended to improve and maintain the quality of learning, each department needs to improve the achievement of learning activities and optimizing readiness of lecturers in the learning process and supporting infrastructure of institutions to prepare an adequate academic.